Associations between the neuron-specific glucocorticoid receptor (NR3C1) Bcl-1 polymorphisms and suicide in cancer patients within the first year of diagnosis. Issue 1 (December 2016) - Park, Subin; Hong, Jin; Lee, Jong-Keuk; Park, Young-Mi; Park, Yangsoon; Jeon, Juri; Ahn, Myeong; Yoon, Se
Abstract Background Cancer diagnosis is associated with an increased suicide risk, particularly within the first 1 year after diagnosis of cancer. Abnormal function of the hypothalamic–pituitary–adrenal axis has been implicated in the pathophysiology of depression and suicide. We examined genetic associations of the functional Bcl-1 polymorphism of (rs41423247) neuron-specific glucocorticoid receptor (NR3C1) gene, with death by suicide in cancer patients. Suicides occurring within a year of cancer diagnosis ('early suicide') were considered separately from those suicides during the second or subsequent year ('late suicide') after cancer diagnosis. Methods The subjects consisted of 343 cancer patients admitted to a general hospital in Seoul, South Korea from 1996 to 2009, of which 182 had died by suicide and 161 were alive on December 31, 2009. Genomic DNA was extracted from formalin-fixed paraffin-embedded tissue sample of patients with cancer. We conducted a case-control association analysis of Bcl-1 polymorphism of NR3C1 gene. Results Subjects carrying the GG genotype of Bcl-1 polymorphism were at increased risk of early suicide when compared to those carrying the CC genotype (OR 3.80, 95 % CI 1.02–14.16, p = .047). Similarly, those individuals carrying the GG genotype (recessive mode) had an increased risk of early suicide relative to the CC or CG genotype (OR 3.71, 95 % CI 1.03–13.43, p = .045). However, there were no differences in the genotype distributions of the NR3C1 Bcl-1 polymorphism between late suicide cases and controls. Conclusions Our findings suggest that the NR3C1 Bcl-1 polymorphisms may be involved in the susceptibility to suicide within the first year after cancer diagnosis among cancer patients in Korean population.